PENGENDALIAN MODAL KERJA SEBAGAI UPAYA MENINGKTKAN PROFITABILITAS KOPERASI (Studi pada Koperasi Unit Desa “BATU” Periode 2012-2014) - Hening Lembarati; . Topowijono; Nengah Sudjana (Fakultas Ilmu Administrasi Universitas Brawijaya, 2016)
Working capital is one of the elements that must be managed properly and wisely by the cooperative. Working capital management of good will have a positive impact on the cooperative, one to increase the profitability desired. Working capital management is done by controlling the working capital to fit the needs that are not advantages and disadvantages. The purpose of this study was to determine how to control working capital in order to enhance profitability at KUD